Analytic solutions of nonlinear Cournot duopoly game - Akio Matsumoto; Mami Suzuki (Discrete Dynamics in Nature and Society)
We construct a Cournot duopoly model with production externality in which reaction functions are unimodal. We consider the case of a Cournot model which has a stable equilibrium point. Then we show the existence of analytic solutions of the model. Moreover, we seek general solutions of the model in the form of nonlinear second-order difference equation.